The Governance Challenges and Strategic Pathways for Sustainable Development of County-Level Football Associations in China - Wang Yulei (Ilmu Inovasi Nusantara, 2024)
The sustainable development of county-level football associations is a requirement set forth by various policy documents from the Party and the State, reflecting the essential principles of Chinese civil sports organizations. Unlike the Chinese Football Association (CFA) and provincial football associations, county-level football associations are characterized by their non-governmental, civic, and amateur nature. This study examines the development of these associations and identifies several significant issues impeding their progress: outdated development concepts, unclear division of power and responsibilities, unequal resource distribution, ineffective roles of leadership bodies, and a lack of clear definitions for the roles of governing bodies. Currently, these associations face the challenge of lagging in development due to these unresolved issues. To address these challenges, it is essential for county-level football associations to revamp their development concepts to align with contemporary needs and expectations. Strengthening the leadership roles within these associations is crucial, as it will provide clear guidance and direction for their activities. Additionally, there is a need to improve the system design to make the management of these associations more efficient and effective. Encouraging the participation of all relevant stakeholders is also vital to form a cohesive and synergistic approach to development. By fostering collaboration among various parties, county-level football associations can leverage diverse resources and expertise, leading to more robust and sustainable growth. The ultimate goal of these recommendations is to promote the endogenous development of county-level football associations. By doing so, these associations can play a pivotal role in enhancing grassroots participation in football, thereby contributing to the broader objective of nurturing a strong mass base for football in China. Through improved governance, resource allocation, and stakeholder engagement, county-level football associations can achieve sustainable development and ensure widespread participation in the sport across the nation